1984
DOI: 10.3406/rfp.1984.1566
|View full text |Cite
|
Sign up to set email alerts
|

Atome, acides-bases, équilibre

Abstract: Atom, acids-bases, equilibria. - From an experiment concerning first year science students (« DEUG » level) located in two different universities, we collected very homogeneous data revealing that entities are generally well known at a descriptive level, but that their interactions are either ignored, or ill perceived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…However, this seemingly straightforward topic on acids and bases has posed many problems to students of various backgrounds. From as early as several decades ago the topic on acids and bases has been reported to be difficult for high school science students (Burns, 1982) who have as a result held several alternative conceptions about acids and bases (Cros et al, 1986;Hand & Treagust, 1991;Nakhleh & Krajick, 1993). Even until recently, several studies have been documented that refer to alternative conceptions about acids and bases that are held by students and teachers alike (Artdej et al, 2010;Chiu, 2004Chiu, , 2007Kala, Yaman & Ayas, 2013;Sheppard, 2006;Drechsler & Van Driel, 2008, 2009.…”
Section: Hcl(aq)  H +mentioning
confidence: 99%
“…However, this seemingly straightforward topic on acids and bases has posed many problems to students of various backgrounds. From as early as several decades ago the topic on acids and bases has been reported to be difficult for high school science students (Burns, 1982) who have as a result held several alternative conceptions about acids and bases (Cros et al, 1986;Hand & Treagust, 1991;Nakhleh & Krajick, 1993). Even until recently, several studies have been documented that refer to alternative conceptions about acids and bases that are held by students and teachers alike (Artdej et al, 2010;Chiu, 2004Chiu, , 2007Kala, Yaman & Ayas, 2013;Sheppard, 2006;Drechsler & Van Driel, 2008, 2009.…”
Section: Hcl(aq)  H +mentioning
confidence: 99%
“…Vu le caractère théorique et traditionnel de l'enseignement de la chimie en Grèce et étant donné que les élèves travaillent surtout au niveau symbolique, nous avons fait une première hypothèse, suivant laquelle il est fort probable que les élèves grecs aient des difficultés de compréhension et de représentation des systèmes de substances (surtout gazeuses) en équilibre chimique, tant au niveau empirique qu'au niveau moléculaire. L'étude des conceptions des élèves par rapport au concept de vitesse de réaction a révélé la difficulté des élèves à saisir l'aspect dynamique sous-jacent à l'équilibre chimique (Cros et al, 1984 ;Garnett et al, 1995 Bien que le déplacement de l'équilibre puisse être décrit par la loi d'action de masse, certains élèves, pourfaire des prévisions concernant le déplacement de l'équilibre, utilisent plutôt la loi de Le Chatelier. Mais l'application de cette loi par des enseignants n'est pas non plus sans problèmes (Quilez-Pardo & Solaz-Portolés, 1995 ;Garnett et al, 1995).…”
Section: Résumé Le But De Cette Recherche éTait La Détection Et L'étuunclassified
“…Several studies reported that the students have a static conception of the equilibrium state (Cros et al, 1984;Maskill and Cachapuz, 1989;Gussarsky and Gorodetzky, 1990;Chiu et al, 2002). Many studies concern shifts of equilibrium, namely, how to determine if and in what direction a chemical system may change after the equilibrium state has been disturbed (see, for example, Hackling and Garnett, 1985;Banerjee, 1991;Hamed et al, 1993;Tyson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%